Preparation of macroporous ion-exchange resin organic amine composite material by using waste plastics and its application in CO2 capture - Liu, Xinmin (Environmental technology, 2023)
Two new types of solid adsorption material (macroporous cation exchange resin (MCER) and macroporous ion-exchange resin organic amine composite material (MCER-DEA)) were prepared from waste television plastics outer shell (WTPS) and used to capture CO2 in flue gas from coal-fired power plants. The results showed that the CO2 adsorption capacity of MCER-DEA was 2.87 mmol/g, while MCER was 1.87 mmol/g. The preparation mechanism and action mechanism of MCER and MCER-DEA was studied by Fourier transform infrared and quantum chemical calculations. The results showed that the electrophilic substitution occurs in between an H atom of meta position on the benzene ring and H2SO4. The electron energy of MCER-DEA was calculated to be 1.14 ev, indicating these MCERs formed acid-base coordination with diethanolamine (DEA). Besides, the electron energy of between MCER and CO2 was 0.27 ev, and the interaction force was dominated by hydrogen bonds. The electron energy of the MCER-DEA and CO2 was 3.02 ev, and the interaction force was mainly controlled by coordination bonds. It indicated that MCER and CO2 were primarily based on physical adsorption, while MCER-DEA and CO2 were mainly based on chemisorption adsorption. Adsorption kinetics studies showed that internal diffusion was a rate-controlling step